2018
DOI: 10.1177/0269215518771127
|View full text |Cite
|
Sign up to set email alerts
|

The Trail Making test: a study of its ability to predict falls in the acute neurological in-patient population

Abstract: This study identifies a simple yet powerful machine learning (Random Forest) based predictive model for an in-patient neurological population, utilizing a single neuropsychological test of cognitive function, the Trail Making test.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Our results revealed significant associations between fixations and measures of divided attention (TMT-B) as well as age. This agrees with findings from earlier studies that reported relationships between TMT-B solving time and visual search measures, attention [64,65], and executive functions (eg, cognitive flexibility [42] and working memory [66]). Visual search and attention are fundamental abilities for solving the puzzle tasks in this study.…”
Section: Comparison With Prior Worksupporting
confidence: 92%
“…Our results revealed significant associations between fixations and measures of divided attention (TMT-B) as well as age. This agrees with findings from earlier studies that reported relationships between TMT-B solving time and visual search measures, attention [64,65], and executive functions (eg, cognitive flexibility [42] and working memory [66]). Visual search and attention are fundamental abilities for solving the puzzle tasks in this study.…”
Section: Comparison With Prior Worksupporting
confidence: 92%
“…Executive functions play an important role in guiding through everyday life including problem-solving and planning and controlling of actions (93). Moreover, they contribute to safe gait as a higher risk of falling was observed in subjects with cognitive impairments including executive functioning deficits (94)(95)(96)(97)(98). Thus, the improvement of executive functioning in this study might be an outcome of high relevance as strengthened executive functions could enhance daily life performance of older adults.…”
Section: Training Effects On Cognitive Functionsmentioning
confidence: 73%
“…32 Regarding the selection of assessment tools, studies have shown that the Functional Independence Measure is an efficient tool in evaluation of the performance of activities of daily living, 17 while the Trail Making Test-A, Digit Symbol Test or Digital Span Test are more efficient in evaluating attention function of patients with cognitive impairment. [18][19][20] Indeed, we used the above assessment tools for the assessment of activities of daily living and attention function.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter the time and the less the number of errors, the better the attention function. 18 (3) Digit Symbol Test (DST). We used the Digit Symbol Test to evaluate the ability of learning and attention conversion of the patients.…”
Section: Outcome Assessment Toolsmentioning
confidence: 99%